(untitled) (REVISTA NODO, 2021)
A spatial analysis of quantitative interactions between theory and practice in urban planning is proposed. Case Study: Sogamoso’s Spatial Plan (called in Colombia Plan de Ordenamiento Territorial) and its urban code (UC). An urban model of development based on discursive principles related to territorial sustainability, regional competitiveness and spatial equity is described. Measurable dimensions are applied upon those principles by using two 3D comparable simulations. The first simulation reproduces the current reality in three zones previously chosen. The second one creates new city forms in those zones by applying the building and construction norms derived from the UC. The comparison of measuring value evidences the emphasis on competitiveness and sustainability in detriment of special equality when urban planning is put into practice.